Transposition and Modulation in the Translation of the Book “La Tachzan” into Indonesian/ التحول الشكلي والتحول المعنوي في ترجمة كتاب "لاتحزن" إلى اللغة الإندونيسية - Munirotun Naimah; Imam Asrori; Irhamni Irhamni (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2021)
The purpose of this research to describe the transposition and modulation in the translation of the book “La Tachzan” into Indonesia. The method used in this research is the descriptive qualitative method. From the data examined, it is found that the shifts in the translation of the book “La Tachzan” are: (1) Transposition must be caused by a system and different language rules, (2) Transposition due to the absence of systems and rules in one language, (3) Transposition due to reasonableness, (4) Transposition of overlap. Modulation shifts are found in the translation of “La Tachzan” (1) Compulsory or linguistic modulation and (2) Non-linguistic modulation.